(untitled) (Cadernos ESP, 2022)
The municipality of Jaguaribe had an increase in the infant mortality rate from 17.86 in 2016 to 22.17 in 2020, different from the downward trend in Brazil and Ceará. Most deaths were from preventable causes, making sustainable strategies necessary for their reduction. Thus, the objective is to reduce infant mortality in Jaguaribe in 2021. Several strategies were carried out, including: Monitoring of pregnant women, training of the multidisciplinary team, implementation of flows for prenatal care and high-risk childbirth, strengthening the search activity and home visits, regulation of pregnant women in a timely manner and implementation of the Maternal, Child and Fetal Death Commission in the municipality. In 2021, there were 02 infant deaths in the municipality, which represents a rate of 4.84, the lowest rate recorded in the last 10 years. The involvement of all health professionals from the health care network’s points of care, acting with a common objective, can be seen.